2012
DOI: 10.5735/086.049.0105
|View full text |Cite
|
Sign up to set email alerts
|

Food Selection by Herbivores and Neighbourhood Effects in the Evolution of Plant Defences

Abstract: A number of studies have reported how neighbouring plants may influence herbivory on palatable or unpalatable plants. Such neighbourhood effects can have important evolutionary consequences as they may either promote the evolutionary stability of plant defences or, alternatively, select against the fixation of plant defences and instead promote a stable polymorphism of palatable and unpalatable plants. These consequences depend on whether the difference in herbivore damage between unpalatable and palatable pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…This pattern has been reported as a type of associational effect; specifically, our example corresponded with the 'neighbor contrast defense' (Bergvall et al 2006;Rautio et al 2012) because we observed less herbivory on the defended phenotype (hairy plants, in our case) when surrounded by undefended individuals. We also found a reciprocal minority advantage in biomass production for the hairy and glabrous plants, which might serve as a potential mechanism to maintain the polymorphism through negative frequency-dependent selection.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This pattern has been reported as a type of associational effect; specifically, our example corresponded with the 'neighbor contrast defense' (Bergvall et al 2006;Rautio et al 2012) because we observed less herbivory on the defended phenotype (hairy plants, in our case) when surrounded by undefended individuals. We also found a reciprocal minority advantage in biomass production for the hairy and glabrous plants, which might serve as a potential mechanism to maintain the polymorphism through negative frequency-dependent selection.…”
Section: Discussionsupporting
confidence: 64%
“…However, it was still possible that density as well as frequency of hairy and glabrous plants might result in the pattern of leaf damage, because our experiment with two neighborhood conditions could not determine the relative importance of density-and frequency-dependent damage on the two plant types (but see Kim and Underwood 2015). We should also note that when herbivores respond nonadditively to plant density (i.e., group effects; Rautio et al 2012) it may lead to similar patterns of damage for an individual plant as those caused by associational effects (see also Hambäck et al 2014 for a theoretical consideration). In future studies, the density and the frequency of the two plant types should be manipulated simultaneously (i.e., response surface design; Damgaard 1998;Inouye 2001) to examine potential interactions between the associational and the resource concentration/ dilution effects on plant damage Hambäck et al 2014).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations